The effectiveness of promotional tools in enhancing customer awareness of Celcom (Malaysia) Berhad / Ahmad Zahim Che Hashim - Che Hashim, Ahmad Zahim (Faculty of Business and Management, 2010)
Promotion is one of the key aspects of the marketing mix. Promotion involves disseminating information about product, product line, brand or company and this variable creates a promotional mix or promotional strategy. Regardless of what types of business the company are in, they need to develop promotional strategies. Company can use promotional mix for their promotional strategies in helping them to communicate clearly to their target market. Through promotional activities also company can inform consumers the important information about their products or services.